2001
DOI: 10.1023/a:1010851130136
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Although expression of liver fatty acid binding protein (L-FABP) modulates cell growth, it is not known if L-FABP also alters cell morphology and differentiation. Therefore, pluripotent embryonic stem cells were transfected with cDNA encoding L-FABP and a series of clones expressing increasing levels of L-FABP were isolated. Untransfected ES cells, as well as ES cells transfected only with empty vector, spontaneously differentiated from rounded adipocyte-like to fibroblast-like morphology, concomitant with mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…The ligand-binding properties and x-ray structure (32,40), isoforms (35), and nutritional and pharmacological regulation (2) of L-FABP are known in great detail. In addition, cell-free systems and transfection studies with L-FABP cDNA have provided hints as to its functions (2,7,9,10,14,33,39,(41)(42)(43). However, no in vivo function can be considered as established, and we believe that a satisfactory understanding of this protein requires an analysis of its role in the native cellular context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ligand-binding properties and x-ray structure (32,40), isoforms (35), and nutritional and pharmacological regulation (2) of L-FABP are known in great detail. In addition, cell-free systems and transfection studies with L-FABP cDNA have provided hints as to its functions (2,7,9,10,14,33,39,(41)(42)(43). However, no in vivo function can be considered as established, and we believe that a satisfactory understanding of this protein requires an analysis of its role in the native cellular context.…”
Section: Discussionmentioning
confidence: 99%
“…Rabbit anti-rat glutathione S-transferase antiserum was purchased from Alpha Diagnostic International (San Antonio, TX), and its crossreactivity with mouse GST was verified by enzyme-linked immunosorbent assay and Western analysis. Rabbit anti-rat L-FABP (14), antimouse SCP-2 (5), and anti-mouse SCP-x (13) were obtained and purified as described in the cited papers; rabbit polyclonal anti-porcine aspartate aminotransferase was generated and purified in the same way; its cross-reactivity with mouse aspartate aminotransferase was confirmed by enzyme-linked immunosorbent assay and Western analysis. Rabbit anti-mouse caveolin-1 (IgG fraction) was obtained from Affinity Bioreagents, Inc. (Golden, CO).…”
Section: Methodsmentioning
confidence: 99%
“…Examination of multiple chambers of cultured hepatocytes with this dual stain assay revealed that cell viability was typically also Ͼ90%. Third, hepatocyte morphology was monitored as previously described (29). Briefly, primary hepatocytes were cultured in serum-free medium supplemented with BSA (4 M) and seeded onto chambered cover glass slides at a cell density of 5 ϫ 10 5 cells/chamber.…”
Section: Methodsmentioning
confidence: 99%
“…The high distribution to the fluorescent LCFAs to cytoplasm reflected the predominant localization of soluble proteins that bind LCFAs, i.e. FABPs (42,44,63). Mock-transfected control L-cells contain an endogenous FABP immunologically distinct from L-FABP (45).…”
Section: L-fabp Expression Stimulates Uptake and Nuclear Distributionmentioning
confidence: 99%